Green Competitive Advantage in The Tourism Industry - Hari Wibisono; Yandra Arkeman; Setiadi Djohar; Mira Maulida (Journal of Scientific Research, Education, and Technology (JSRET), 2023)
Despite the significant growth of Indonesia's tourism sector, its competitive standing in the industry is still comparatively disadvantaged when compared to neighboring countries like Singapore, Malaysia, and Thailand. Previous empirical studies have identified a significant truth: the emergence of green tourism and a shift in tourism demand. Our research endeavors to formulate a sustainable tourism development strategy for Indonesia with the ultimate goal of attaining a green competitive advantage. Mixed methods were employed to conduct this study. For model analysis, Structural Equation Modeling (SEM-PLS) is utilized. Primary data were obtained directly from research subjects via questionnaires and interviews administered to 60 samples. SEM-PLS was utilized to manage the collected data. Secondary data were obtained from literature from previous studies. In conjunction with the Analytical Hierarchy Process (AHP), the outcomes of the analysis are utilized to ascertain policy priorities for the development of strategies pertaining to the tourism industry in Indonesia. The implications of these results extend beyond the realm of corporate strategic management and its practical implementations to the dynamic tourism sector, where GCA can be obtained. Policy proposals in priority areas were additionally put forth with the aim of fostering the growth of Indonesian tourism.